2020
DOI: 10.1186/s42269-020-00364-2
|View full text |Cite
|
Sign up to set email alerts
|

Position and dimensions of the mental foramen and presence of the anterior loop in the Egyptian population: a retrospective CBCT study

Abstract: Aim Understanding the mental foramen (MF) position and prevalence and location of the anterior loop (AL) is important during clinical and surgical procedures close to the mental foramen to avoid damage to the neurovascular bundle. The current study was done to determine the location of the MF, its distance from the inferior border of the mandible, and prevalence of AL in Egyptian population using cone beam computed tomography (CBCT). Methods A retrospective analysis of CBCT images was done in this study. Imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…However, there were studies on the topography of the MnF in the vertical plane in which only the distance between the MnF and the IB or the distance to the SB were highlighted: such observations did not enable an assessment of the MnF position relative to the mandibular body height [23][24][25].…”
Section:  Discussionmentioning
confidence: 99%
“…However, there were studies on the topography of the MnF in the vertical plane in which only the distance between the MnF and the IB or the distance to the SB were highlighted: such observations did not enable an assessment of the MnF position relative to the mandibular body height [23][24][25].…”
Section:  Discussionmentioning
confidence: 99%
“…Thirteen studies used a small FOV, 12 24 25 26 27 28 29 30 31 32 33 34 35 15 studies used a medium FOV, 14 23 26 36 37 38 39 40 41 42 43 44 45 46 47 and 16 studies used a large FOV. 1 11 21 22 44 46 48 49 50 51 52 53 54 55 56 Moreover, 30 studies used a voxel size of less than 0.3 mm, 11 12 13 14 22 24 25 28 29 30 31 33 34 35 39 40 41 42 44 45 47 49 50 51 55 57 58 59 60 61 whereas 26 studies used voxels that were 0.3 mm or larger. 1 10 14 21 23 26 27 …”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, Shalash et al 12 found that the mean distance from the inferior border was 10.08 mm in females and 10.55 mm in males, with no significant difference between the genders in their research on an Egyptian population to estimate the position and size of the MF via CBCT.…”
Section: Discussionmentioning
confidence: 98%